Analysis of factors associated with COVID-19 mortality in a triple border city (Research, Society and Development, 2022)
This study aims to analyze the factors associated with mortality by COVID-19 in a city of the triple border. This is a cross-sectional, descriptive and exploratory research of quantitative nature, to be carried out with the compulsory notification forms of deaths by coronavirus, the epidemiological surveillance of the municipality of Foz do Iguaçu-PR. The data were grouped into several categories: sex, age, color, nationality, education, need for hospitalization, type of transmission and morbidities. Thus, through this study, we identified higher mortality in the male group, aged between 70 and 79 years, white, Brazilian nationality, low education, need for hospitalization, type of community transmission and among the comorbidities were more present: hypertension, BMI above the appropriate, diabetes, cardiovascular and pulmonary diseases. Some individuals presented one or more comorbidity, the rate of people without comorbidities or under investigation were low. Thus concluding that these factors associated with the coronavirus showed influence on the mortality of these individuals.